Tank Cleaning Process dalam Menunjang Kelancaran Pemuatan Jet A-1 di Kapal Mt. Andhika Vidyanata - Widar Bayu Wantoro; Fafa Bagaskoro (Jurnal Maritim Polimarin, 2021)
Proper loading space preparation is an important factor in the loading and unloading activities of a tanker. An unprepared tank for loading space will result in losses for the company, for that it requires close cooperation between the company. This research was conducted to determine the factors that cause the less optimal implementation of tank cleaning on the ship MT. Andhika Vidyanata. The data collection technique used was the observation technique. The data processing technique used in this research is the editing process and the data analysis method is descriptive qualitative. The problem finding obtained from the research is that the implementation of tank cleaning activities on the ship MT. Andhika Vidyanata. is not optimal. Lack of coordination, supervision, communication and maintenance of cleaning equipment for loading rooms is the cause of the tank cleaning process not running optimally. Efforts that must be made to overcome the cleaning process for loading spaces in order to run optimally are to improve ship crew coordination and carry out routine maintenance of supporting equipment for cleanliness of cargo spaces. The results obtained from this study are to optimize the implementation of tank cleaning in order to prevent delays in loading on board.